2019
DOI: 10.1111/1365-2656.12962
|View full text |Cite
|
Sign up to set email alerts
|

Weak effects of geolocators on small birds: A meta‐analysis controlled for phylogeny and publication bias

Abstract: 1. Currently, the deployment of tracking devices is one of the most frequently used approaches to study movement ecology of birds. Recent miniaturization of lightlevel geolocators enabled studying small bird species whose migratory patterns were widely unknown. However, geolocators may reduce vital rates in tagged birds and may bias obtained movement data.2. There is a need for a thorough assessment of the potential tag effects on small birds, as previous meta-analyses did not evaluate unpublished data and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 104 publications
3
79
0
Order By: Relevance
“…Although sample sizes were often small, as is typical for such exploratory studies (see Brlík et al . for an overview), we nonetheless have contributed significantly to the knowledge of migration routes and timing in this species. First, we have confirmed that western European breeders migrate on a western route to non‐breeding regions in West Africa, and that eastern European birds migrate on an eastern route to southern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Although sample sizes were often small, as is typical for such exploratory studies (see Brlík et al . for an overview), we nonetheless have contributed significantly to the knowledge of migration routes and timing in this species. First, we have confirmed that western European breeders migrate on a western route to non‐breeding regions in West Africa, and that eastern European birds migrate on an eastern route to southern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…We deployed solar geolocators (Intigeo‐W65A9, Migrate Technology Ltd) on 44 sanderlings in June–July 2013 and 2015 at Zackenberg (26 males and 18 females) and on eight sanderlings in June–July 2013 in Karupelv Valley (2 males, 3 females and 3 of unknown sex). The geolocators were attached to a leg flag, which did not affect annual return rates (Brlík et al, ; Weiser et al, ). We retrieved eight of the 52 geolocators (15%), seven of which we were able to download data from.…”
Section: Methodsmentioning
confidence: 99%
“…Four fixed effects models were considered: sex, winter area and additive and interaction effects of sex and winter area. The geolocators were attached to a leg flag, which did not affect annual return rates (Brlík et al, 2019;Weiser et al, 2016). We retrieved eight of the 52 geolocators (15%), seven of which we were able to download data from.…”
Section: Age Of First Northward Migrationmentioning
confidence: 99%
“…For instance, supposedly harmless devices caused a fivefold decrease in foraging efficiency of Magellanic penguins (Wilson, Kreye, Lucke, & Urquhart, 2004) and heavy collars reduced survival of migratory caribou by 18% (Rasiulis, Festa-Bianchet, Couturier, & Côté, 2014). Recent meta-analyses show that tracking devices have a negative effect on different traits in birds (Barron, Brawn, & Weatherhead, 2010;Bodey et al, 2017;Brlík et al, 2019). These effects can be partially mitigated, for instance by the mode of attachment (White et al, 2013) and by minimizing tag size (Bodey et al, 2017;Casper, 2009).…”
mentioning
confidence: 99%